Cellulose-based interdigitated electrodes for rivaroxaban apta-sensing in blood plasma - Rokhsareh Ebrahimi; Mohammad Hasanzadeh; Azadeh Nilghaz; Nasrin Shadjou (Carbohydrate Polymer Technologies and Applications)
Monitoring of Rivaroxaban (RIV) at trace levels in patients at risk of atrial fibrillation disorders (AFD) is of great importance. In this study, for the first time, a miniaturized interdigitated electrode (mIDE) biosensor was fabricated using superconducting silver nano ink for the detection of RIV in human plasma. The biosensor exhibited a linear detection range of 10–1000 nM with a lower limit of quantification of 10 nM. The specificity of the biosensor was also validated through square wave voltammetry in the presence of potential interfering compounds, confirming its selectivity and reliability. Based on obtained results, integration of biosensor technology and flexible electronics enhance the mIDE performance, making it a promising tool for real-time monitoring of RIV levels in clinical settings, especially for atrial fibrillation. This low-cost device shows great potential for the pharmaceutical analysis.